Terrorist's Creed - Griffin, R. author. aut Link
X, 270 p.
Keywords: Terrorist's Creed casts a penetrating beam of empathetic understanding into the disturbing and murky psychological world of fanatical violence, explaining how the fanaticism it demands stems from the profoundly human need to imbue existence with meaning and transcendence.